2013
DOI: 10.1038/jes.2013.37
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of diet to aggregate arsenic exposures—An analysis across populations

Abstract: The relative contribution of dietary arsenic (As) to aggregate daily exposure has not been well-characterized, especially in relation to the current EPA maximum contaminant level (MCL) of 10 p.p.b. for As in drinking water. Our objectives were to: (1) model exposure to inorganic and total As among non-seafood eaters using subject-specific data, (2) compare the contribution of food, drinking and cooking water to estimated aggregate exposure in households with variable background tap water As levels, and (3) des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
60
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(62 citation statements)
references
References 42 publications
0
60
0
2
Order By: Relevance
“…Defining iAs exposure through water arsenic level alone likely underestimates total iAs exposure, especially in the US, because food can be an important source of arsenic exposure. This is particularly true in instances when water arsenic levels are low because the contribution of dietary arsenic is inversely proportional to water arsenic levels (Kurzius-Spencer et al, 2014;Gilbert-Diamond et al, 2011;Petito Boyce et al, 2008). For example, Kurzius-Spencer et al (2014) reported that diet was a substantial contributor to total and iAs intake in surveys of residents of Arizona and a representative sample of the entire US population.…”
Section: Sources Of Arsenic Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…Defining iAs exposure through water arsenic level alone likely underestimates total iAs exposure, especially in the US, because food can be an important source of arsenic exposure. This is particularly true in instances when water arsenic levels are low because the contribution of dietary arsenic is inversely proportional to water arsenic levels (Kurzius-Spencer et al, 2014;Gilbert-Diamond et al, 2011;Petito Boyce et al, 2008). For example, Kurzius-Spencer et al (2014) reported that diet was a substantial contributor to total and iAs intake in surveys of residents of Arizona and a representative sample of the entire US population.…”
Section: Sources Of Arsenic Exposurementioning
confidence: 99%
“…This is particularly true in instances when water arsenic levels are low because the contribution of dietary arsenic is inversely proportional to water arsenic levels (Kurzius-Spencer et al, 2014;Gilbert-Diamond et al, 2011;Petito Boyce et al, 2008). For example, Kurzius-Spencer et al (2014) reported that diet was a substantial contributor to total and iAs intake in surveys of residents of Arizona and a representative sample of the entire US population. In households with 10 mg/L total iAs in water, 54-85% of the daily iAs exposure came from food; in homes with >10 mg/L total iAs in water, about 30% of total iAs exposure came from food sources.…”
Section: Sources Of Arsenic Exposurementioning
confidence: 99%
“…Relatively recent studies that report solely As content of specific food groups or population consumption estimates of specific arseniccontaining foods without accompanying As concentration data or biomarker information (e.g., urinary, blood, or nail As values) were excluded from further consideration since both estimated intake and uptake concentration values are needed in order to estimate bioavailability (Lynch et al, 2014;Nacano et al, 2014;Kurzius-Spencer et al, 2014;Del Razo et al, 2002;Bundschuh et al, 2012;Gilbert-Diamond et al, 2011;Torres-Escribano et al, 2008;Mansilla-Rivera et al, 2014).…”
Section: Dietary Arsenicmentioning
confidence: 99%
“…Overall, dietary As accounts for approximately 70% of iAs intake with a range of 1-20 μg/day. Numerous studies assessing U.S. population dietary and multi-pathway As exposures have demonstrated that diet is the primary contributor to total and inorganic As exposure when drinking water As levels are not elevated (Meacher et al, 2002;Tsuji et al, 2007;Georgopoulos et al, 2008;Xue et al, 2010;Kurzius-Spencer et al, 2014). In these studies potential variation in RBA of As among foods was not considered contributing to uncertainty in health risk model outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…5 Foods including rice, rice-based products, and apple juice also can be contaminated with inorganic arsenic, and diet may constitute a sizeable proportion of some people's total exposure. 6 Arsenic is not currently regulated in food, although the U. S. Food and Drug Administration recently proposed guidance for industry that levels of inorganic arsenic in apple juice not to exceed 10 ppb. 7 In addition to cancer, inorganic arsenic has been linked to nonmalignant respiratory illnesses including chronic bronchitis, chronic obstructive pulmonary disease, and bronchiectasis in people, with lung cancer and bronchiectasis particularly linked to exposure in utero or during early childhood.…”
mentioning
confidence: 99%